Role of Insulin-Like Growth Factor Binding Protein-3 in 1, 25-Dihydroxyvitamin-D3-Induced Breast Cancer Cell Apoptosis - C. Brosseau; G. Pirianov; K. W. Colston (International Journal of Cell Biology)
Insulin-like growth factor I (IGF-I) is implicated in breast cancer development and 1, 25-dihydroxyvitamin D3 (1, 25-D3) has been shown to attenuate prosurvival effects of IGF-I on breast cancer cells. In this study the role of IGF binding protein-3 (IGFBP-3) in 1, 25-D3-induced apoptosis was investigated using parental MCF-7 breast cancer cells and MCF-7/VDR cells, which are resistant to the growth inhibitory effects of 1, 25-D3. Treatment with 1, 25-D3 increased IGFBP-3 mRNA expression in both cell lines but increases in intracellular IGFBP-3 protein and its secretion were observed only in MCF-7. 1, 25-D3-induced apoptosis was not associated with activation of any caspase but PARP-1 cleavage was detected in parental cells. IGFBP-3 treatment alone produced cleavage of caspases 7, 8, and 9 and PARP-1 in MCF-7 cells. IGFBP-3 failed to activate caspases in MCF-7/VDR cells; however PARP-1 cleavage was detected. 1, 25-D3 treatment inhibited IGF-I/Akt survival signalling in MCF-7 but not in MCF-7/VDR cells. In contrast, IGFBP-3 treatment was effective in inhibiting IGF-I/Akt pathways in both breast cancer lines. These results suggest a role for IGFBP-3 in 1, 25-D3 apoptotic signalling and that impaired secretion of IGFBP-3 may be involved in acquired resistance to vitamin D in breast cancer.